Neonatal kangaroo care - What we know and how we can improve its practice: An evidence review. Issue 6 (December 2022) - Cunningham, Colette; Patton, Declan; Moore, Zena; O'Connor, Tom; Bux, Dhani; Nugent, Linda
Abstract: Purpose: The purpose of this evidence search was to review past and current kangaroo care practice and explore the Iiterature relating to improving kangaroo care for preterm infants. Method: A literature review of evidence was undertaken in order to answer pre specified questions. The literature search was undertaken on CINAHL, Google Scholar and Pubmed. Key search terms were kangaroo care, skin to skin care, kangaroo mother care, preterm infants, benefits, practices, enablers and education. Conclusion: A lack of training and formal education greatly inhibits kangaroo care provision in the neonatal environment. The level of confidence a nurse has in their ability to decide whether the infant is clinically stable or not, will determine if kangaroo care is offered. Neonatal nurse education is imperative in order to improve kangaroo care practice in the clinical setting.